2013
DOI: 10.3961/jpmph.2013.46.s.s12
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Physical Activity in Mental Disorders: Clinical and Experimental Evidence

Abstract: Several epidemiological studies have shown that exercise (EX) and physical activity (PA) can prevent or delay the onset of different mental disorders, and have therapeutic benefits when used as sole or adjunct treatment in mental disorders. This review summarizes studies that used EX interventions in patients with anxiety, affective, eating, and substance use disorders, as well as schizophrenia and dementia/mild cognitive impairment. Despite several decades of clinical evidence with EX interventions, controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(137 citation statements)
references
References 85 publications
6
121
1
9
Order By: Relevance
“…Some studies have shown that exercise and physical activity can prevent or delay the onset of different mental disorders, and that they have therapeutic benefits when used as the sole or adjunct treatment for mental disorders. [14][15][16] Therefore, these data show a possibility for preventive action that could be taken.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that exercise and physical activity can prevent or delay the onset of different mental disorders, and that they have therapeutic benefits when used as the sole or adjunct treatment for mental disorders. [14][15][16] Therefore, these data show a possibility for preventive action that could be taken.…”
Section: Resultsmentioning
confidence: 99%
“…One of the strongest determinants of psychological well-being, as well as physical health outcomes, is exercise (Penedo & Dahn, 2005). Systematic review evidence suggests that physical activity interventions can lead to improvements in positive affect (Reed & Buck, 2009), stress-related illness (Geber & Pühse, 2009), and clinical mental disorders (Zschucke, Gaudlitz, & Ströhle, 2013). Vigorous intensity activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, regular physical activity is associated with lower rates of numerous disorders including depression, panic disorder, agoraphobia, social phobia, and specifi c phobia 1 ; a large body of evidence indicates that exercise improves anxiety and depression 2 ; and accruing evidence suggests that aerobic exercise is associated with neurogenesis and improved memory function. 3 A recent study also demonstrated that the association between depressive symptoms and cardiovascular events in a sample of 1,000 outpatients with coronary artery disease was largely explained by self-reported physical inactivity.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%